2019
DOI: 10.24294/jipd.v3i1.1083
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of public capital on growth: An extension of the World Bank Long-Term Growth Model

Abstract: To analyze the effect of an increase in the quantity or quality of public investment on growth, this paper extends the World Bank’s Long-Term Growth Model (LTGM), by separating the total capital stock into public and private portions, with the former adjusted for its quality. The paper presents the LTGM public capital extension and accompanying freely downloadable Excel-based tool. It also constructs a new infrastructure efficiency index, by combining quality indicators for power, roads, and water as a cardina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Also, using the dynamic panel model, Boopen (2006) found that transport capital contributed significantly to the economic growth of Sub-Saharan African countries and Small Island Developing States. Employing the World Bank's Long-Term Growth Model (LTGM), Devadas and Pennings (2019) analyzed the effects of an increase in the quantity or quality of public investment on growth. They found that a permanent 1% GDP increase in public investment increases growth by around 0.1 to 0.2 percentage points.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, using the dynamic panel model, Boopen (2006) found that transport capital contributed significantly to the economic growth of Sub-Saharan African countries and Small Island Developing States. Employing the World Bank's Long-Term Growth Model (LTGM), Devadas and Pennings (2019) analyzed the effects of an increase in the quantity or quality of public investment on growth. They found that a permanent 1% GDP increase in public investment increases growth by around 0.1 to 0.2 percentage points.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The theoretical approach, based on Devadas and Pennings (2018), uses a constant elasticity production function to derive the marginal productivity of BRI investments. This model assumes that the impact of additional investment on growth declines as the public capital stock rises.…”
Section: Imentioning
confidence: 99%
“…The literature also presents two very different approaches to estimate the impact: one is theory based and the second empirical. This paper presents both approaches: First, it applies the marginal productivity of efficiency-adjusted public investment to estimate the impact of investment on growth in the medium term, following Devadas and Pennings (2018). Second, the paper estimates the impact on growth of physical infrastructure, controlling for a broad set of variables, following Calderon (2009).…”
Section: Adding the Investment-growth Nexusmentioning
confidence: 99%
See 2 more Smart Citations